Electronic recording of transfusion‐related patient observations: a comparison of two bedside systems. Issue 8 (27th September 2017) - Staples, S.; Noel, S.; Watkinson, P.; Murphy, M. F.
Abstract : Background and Objectives: Vital sign observations should be monitored before, during and after transfusion to enable adverse events to be identified, but surveys in the UK show poor compliance with good practice. At the Oxford University Hospitals, there are two electronic bedside processes for recording observations; BloodTrack Tx (Haemonetics Corp.), the routine electronic transfusion process and a locally developed process, the System for Electronic Nursing Documentation (SEND) with integrated 'track and trigger' calculation for monitoring vital signs. The purpose of this study was to evaluate the conduct of patient observation monitoring for blood transfusion using two electronic bedside processes. Materials and Methods: This study examined the observations recorded during 200 single red cell unit transfusions. Results: 186/200 (93%) transfusions had pretransfusion observations recorded using BloodTrack Tx. Mid‐transfusion checks were performed during 133/200 (67%) of transfusions, of these checks most (87/200 (44%)) were documented as 'no apparent change' in observations. End transfusion observations were performed using BloodTrack Tx in 178/200 (89%). Both systems were frequently used, and staff had a preference for using SEND first for documenting the pretransfusion observations (102/116 (88%)) and at the end of a transfusion (75/115 (65%)). Conclusion: Electronic bedside systems result in improved monitoring of transfusion‐related observations compared to manual processes based on data from UK surveys. There is increasing use of electronic systems in clinical practice; linkage between these two systems would prevent wasteful duplication of observations and could provide improved early warning of adverse events to transfusion compared to manual processes.